"Farewell" to Prognosis in Shared Decision-Making. (June 2020) - Johnson, Robert F.
Whether because of a cultural pattern or personal preference, palliative care clinicians encounter persons approaching the end of life who wish to limit or forego prognostic information relating to their situation. This scenario has received attention in a recent motion picture as well as a newly available advance directive modification—the Prognosis Declaration form. The ordinary expectation for end-of-life shared decision-making with a capable person is clinician disclosure of the best effort at prognostic assessment. The optimal match between the expressed values, goals, and preferences of the person with available clinician expertise is hopefully achieved. For the clinician, a person's choice to modify information disclosure and participation in shared decision-making represents a significant challenge of balancing key ethical principles of intervention with tolerance and compassion for these different preferences. Attention to communication strategies that elicit and appropriately reassess individual information and decision-making wishes, flexibility in information disclosure patterns with capable persons and their representatives, and recognition that a respect for autonomy includes the choice to opt out can approach this challenge while providing compassionate and ethical end-of-life care.